How Digital Communication Transparency and Public Trust Shape Crisis Communication through Public Engagement - Kumalasari, Ana; Musa, Hussein Gibreel; Garad, Askar; Emovwodo, Silas Oghenemaro; Aditasari, Krisnayanti (Universitas Muhammadiyah Yogyakarta, 2024)
This study examines the influence of digital communication transparency and public trust on crisis communication effectiveness in local governments in the MENA region, with public engagement as a mediator. Using a quantitative approach and Structural Equation Modelling (SEM) with data from 228 respondents, findings indicate that while transparency enhances public engagement significantly, trust alone does not directly boost engagement. Public engagement plays a vital mediating role, strengthening the effects of both transparency and trust on communication effectiveness. These results suggest that MENA governments should prioritize strategies fostering public participation alongside transparency to improve crisis communication outcomes. By actively engaging citizens, governments can enhance crisis management, strengthen public trust, and achieve more effective communication. This study contributes to the literature by underscoring the critical role of public engagement in crisis communication strategies.